Hubungan Aktivitas Fisik Dengan Kebahagiaan Pada Masa Pandemi Covid-19 - Nesi Nesi (PT WIM Solusi Prima, 2022)
The Covid-19 pandemic causes changes in daily activities so that a person limits their activities. This is considered to have an effect on a person's mood. Objective: To investigate the relationship between physical activity and happiness in young adults during the Covid-19 pandemic. Methods: This study used a cross-sectional study method. Data was collected through a google form containing a demographic questionnaire, the International Physical Activity Questionnaire (IPAQ) and the Subjective Happiness Scale (SHS). Results: there are differences in happiness based on the level of physical activity, someone with the highest level of physical activity shows the greatest happiness. However, no significant difference has been found between the share and the level of physical activity. Pandemi Covid-19 menyebabkan terjadinya perubahan dalam kegaiatan sehari-hari sehingga seseorang membatasi dirinya untuk beraktivitas. Hal ini dianggap berpengaruh terhadap suasana hati seseorang. Tujuan: Menyelidiki hubungan antara aktivitas fisik dengan kebahagiaan pada dewasa muda selama pandemic Covid-19. Metode: Penelitian ini menggunakan metode cross-sectional study. Data dikumpulkan melalui google form yang berisi kuesioner demografis, International Physical Activity Questionnaire (IPAQ) dan Subjective Happiness Scale (SHS). Hasil: terdapat perbedan kebagaiaan berdasarkan tingkat aktivitas fisik, seseorang dengan tingkat tingkat aktivitas fisik paling tinggi menunjukan kebahagiaan paling besar. Meskipun demikian belum ditemukan perbedaan significant antara kebagian dan tingkat aktivitas fisik.